Targeting Major Signaling Pathways of Bladder Cancer with Phytochemicals: A Review. (31st December 2021) - Chestnut, Connor; Subramaniam, Dharmalingam; Dandawate, Prasad; Padhye, Subhash; Taylor, John; Weir, Scott; Anant, Shrikant
Abstract: Bladder cancer is the 9 th most prevalent cancer worldwide and carries a protracted treatment course with significant patient expense, morbidity, and mortality. Over 95% of bladder cancers arise from the urothelium and invade into the underlying muscle layer before metastasizing. Trans-urethral resection and BCG therapy is the current first-line treatment for non-muscle invasive bladder cancer but carries a high rate of tumor recurrence and progression. The poor outcomes associated with advanced disease indicate the urgent need for new and improved treatment strategies. There is increasing investigation into the molecular signaling pathways involved in bladder cancer pathogenesis with the goal of uncovering potential therapeutic targets. This article reviews the major signaling pathways implicated in bladder cancer, including PI3K/AKT/mTOR, Ras/Raf/MEK/MAPK, NF-κB, Wnt/β‐catenin, Notch, Hedgehog, Hippo, JAK/STAT, and TGF-β as well as major cellular receptors central to cancer pathophysiology, including EGFR, Her2, FGFR, and VEGF. We also discuss various naturally occurring phytochemicals that show evidence of targeting these molecular pathways including curcumin, resveratrol, green tea polyphenols, sulforaphane, erucin, genistein, genipin, baicalein, quercetin, isoquercitin, vitamin E, parthenolide, dioscin, triptolide, kaempferol, pterostilbene, isoliquiritigenin, and escin. This review highlights the potential use of these compounds in treatment of bladder cancer.